2006
DOI: 10.1007/s00104-006-1278-0
|View full text |Cite
|
Sign up to set email alerts
|

Embolisierende Thrombose bei Fehlbildung der V. cava inferior

Abstract: Persistent left-sided inferior vena cava (VCI) is a rare venous anomaly, its prevalence being estimated at 0.2-0.5%. Thrombotic occlusion of a VCI has been reported in only a few of these cases. We report the case of a 24-year old woman who suffered an acute thrombosis in a left-sided VCI and recurrent pulmonary embolism. After thrombectomy the course was uneventful. The diagnostic approach and the treatment strategy are discussed with reference to the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…[7] Rudolph et al reported a case of a 24-year-old woman who suffered an acute thrombosis in a left-sided IVC and recurrent PE. [8] In our patient, a contrast CT ruled out PE (Fig. 1C, F).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…[7] Rudolph et al reported a case of a 24-year-old woman who suffered an acute thrombosis in a left-sided IVC and recurrent PE. [8] In our patient, a contrast CT ruled out PE (Fig. 1C, F).…”
Section: Discussionmentioning
confidence: 70%
“…Other studies have also reported right-sided occlusion in association with left-sided IVC. [8][9][10] Hence, congenital anomalies of IVC should be suspected when a patient with no significant medical history presents with a right-sided lower extremity DVT.…”
Section: Discussionmentioning
confidence: 99%